Identify Consumer Behavior in Choosing Delivery Services in Shopping in the Digital Era - Rina Indrayani (Kusuma Negara Business School, 2021)
The digital age makes all parties deal with delivery services, both e-commerce, and consumers. Not a few confused consumers choose a delivery service that is able to fulfill their desires. The purpose of this research is how to choose a delivery service using the selected criteria. The method used is The Hierarchical Analysis Process where this method can help determine the order of criteria used. Based on the results of the study, the order of criteria used by consumers is the time of collection and delivery of goods amounting to -1,646 stopover time -1,607 handling of loss and damage of goods -1,632 billing system -1,722 and accuracy of information of -1,543, where the results show JNE with a final conclusion rate of 0,392 then SICEPAT 0,342 and the last J&T which is 0,290.